Muslim-Christian Debates in the Subcontinent: A Research Review - Abbas, Dr. Syed Toqeer; Riaz, Dr. Muhammad (Al-Irfan, 2023)
Subcontinent is a multi-religious territory and Hinduism is the most ancient religion of this land which is divided into more sects. When Christianity started here during the first century AD the Indians accepted it and bowed the knee before it. Islam was introduced in the Subcontinent because of Arabian traders. In the 8th century, the Arabian government was established here. The Christians, being the people of the Book, created more problems for the Muslims because of some similarities. That is why the Muslims had to face their objections and prove Islam as a true divine religion. Mughal emperor Akbar started Muslim-Christian debates and after him, his son Jahangir held on to this practice. Their religious policies upreared Christianity in the Subcontinent. Shāh Jahān got over this situation and encouraged the Muslim-converted people by changing the law. Muslim-Christian debates were in full swing during the British period. It was the time when Christian ecclesiasts burnt the candle at both ends to convert the Muslims to Christianity.